Potential airborne asbestos exposures in dentistry: a comprehensive review and risk assessment. (21st April 2021) - Ierardi, A. Michael; Mathis, Claire; Urban, Ania; Jacobs, Neva; Finley, Brent; Gaffney, Shannon
Abstract: Chrysotile was formerly used in the manufacture of casting ring liner (CRL) and periodontal dressing powder (PDP). The purpose of this study was to describe the potential for airborne asbestos exposure among dental professionals who may have used these products and to assess their risk of asbestos-related disease (ARD). Task-specific exposure data associated with CRL and PDP were identified and compared to regulatory standards for asbestos and health-based benchmarks. Personal airborne fiber concentrations ranged from 0.008–3.5 f/cc by PCM (duration: 3–420 minutes) for CRL (tearing, placement), and from <0.0044–<0.297 f/cc by PCM (duration: 5–28 minutes) for PDP (mixing). Eight-hour time-weighted average (TWA) exposures were calculated using the reported task-based airborne fiber concentrations and associated sampling durations. For CRL tasks, the upper-bound calculated 8-hour TWA of 0.022 f/cc (tearing, placement) did not exceed regulatory standards for asbestos (≥0.1 f/cc). All samples collected during the mixing of PDP resulted in non-measurable fiber concentrations. The greatest estimated cumulative asbestos exposure for dental professionals using CRL (tearing, placement) of 0.33 f/cc-years is well below "best estimate", published chrysotile no-observed-adverse-effect-levels (NOAEL) for ARD (lung cancer = 89–168 f/cc-years; pleural mesothelioma = 208–415 f/cc-years). As such, the use of asbestos-containing CRL and/or PDP is not expected to pose an increased risk of ARD among dental professionals. This conclusion is consistent with the lack of an increased risk of ARD reported in epidemiological studies of these occupations.